Structural Insights on Tiny Peptide Nucleic Acid (PNA) Analogues of miRNA-34a: An in silico and Experimental Integrated Approach - Moccia, Maria; Mercurio, Flavia Anna; Langella, Emma; Piacenti, Valerio; Leone, Marilisa; Adamo, Mauro F. A.; Saviano, Michele (Frontiers in Chemistry, 2020)
MicroRNAs (miRNAs) are widely considered as master modulators of human genome being involved in both physiological and pathological cellular processes. In particular, miRNAs play an oncogenic or tumour-suppressor role in cancer and an intervention on dysregulated expression levels in many tumours could become a reliable therapeutic approach for cancer treatment. In the present work, we have further explored the use of peptide nucleic acids (PNAs) as potential analogues for the endogenous tumour-suppressor miRNA-34a. In particular, the region from base 1 to 8 of miRNA-34a (corresponding to the “seed” region) was reproduced in the form of an 8-mer PNA fragment (tiny PNA); its structural properties, along with its interaction with target 3’UTR MYCN mRNA, were studied through spectroscopic techniques (CD, UV, NMR) and molecular dynamics simulations. Preliminary uptake assay of PNA in Neuroblastoma Kelly cells was also carried out. The reported results corroborate the interest towards the use of PNAs based analogues as effective RNA targeting agents and we wish to shed light on structural requirements to design chimeric PNA/RNA sequences, fine-tune properties and possibly gain interaction with RISC complex.